Photonic information processing beyond Turing: an optoelectronic implementation of reservoir computing - Larger, L.; Soriano, M. C.; Brunner, D.; Appeltant, L.; Gutierrez, J. M.; Pesquera, L.; Mirasso, C. R.; Fischer, I. (Optics express, 2012)
Many information processing challenges are difficult to solve with traditional Turing or von Neumann approaches. Implementing unconventional computational methods is therefore essential and optics provides promising opportunities. Here we experimentally demonstrate optical information processing using a nonlinear optoelectronic oscillator subject to delayed feedback. We implement a neuro-inspired concept, called Reservoir Computing, proven to possess universal computational capabilities. We particularly exploit the transient response of a complex dynamical system to an input data stream. We employ spoken digit recognition and time series prediction tasks as benchmarks, achieving competitive processing figures of merit.